Fungsi Upacara Adat Tentobus pada Suku Dayak Pesaguan di Kecamatan Tumbang Titi Kalimantan Barat - Aline Rizky Oktaviari Satrianingsih; Regaria Tindarika; Mega Cantik Purti Aditya; Fernandus Deo Decapriyo (SENDRATASIK UNP, 2023)
The Tentobus traditional ceremony procession is usually carried out by the Dayak Pesaguan ethnic in West Kalimantan Province. The Pesaguan Dayak ethnic is close to nature and often carries out activities by working together. They respect the norms and rules that are still attached, so that the activities they carry out for survival are accompanied by rituals as expressions of gratitude and requests for permission. Based on believed folklore, the traditions and rituals passed down from ancestors are related to the culture brought by the Majapahit era and are part of the civilization of the Dayak Pesaguan tribe in Tumbang Titi District, Ketapang Regency. This research is descriptive qualitative research with an anthropological approach. Researchers conducted interviews and documentation studies. Data collection through interviews with sources and literature study. The credibility test was carried out by extending observations and data triangulation. The results of this research state that the Tentobus Traditional Ceremony aims to cleanse oneself and reject evil as well as cleanse oneself from mistakes in the past year, the old year, and the following year. The Tentobus Traditional Ceremony process is carried out sequentially with different procession sequences. Overall, each procession boils down to expressions of gratitude and protection.